Computational design of light and strong high entropy alloys (HEA): Obtainment of an extremely high specific solid solution hardening. (November 2018) - Menou, Edern; Tancret, Franck; Toda-Caraballo, Isaac; Ramstein, Gérard; Castany, Philippe; Bertrand, Emmanuel; Gautier, Nicolas; Rivera Díaz-Del-Castillo, Pedro Eduardo Jose
Abstract: A multi-objective optimisation genetic algorithm combining solid solution hardening (SSH) and thermodynamic modelling (CALPHAD) with data mining is used to design high entropy alloys (HEAs). The approach searches for the best compromise between single-phase stability, SSH and density. Thousands of Pareto-optimal base-centred cubic (BCC) HEAs are designed. Al35 Cr35 Mn8 Mo5 Ti17 (at.%) is chosen for experimental validation. The alloy was cast and characterised. Its microstructure consists of large grains of a single disordered solid solution displaying a Vickers hardness of 6.45 GPa (658 HV) and a density below 5.5 g/cm 3 ; uniquely combining exceptional hardness with medium density. Graphical abstract: Unlabelled Image